TRANSPORT DIPLOMACY planning narratives and mobility cooperation. - Ampleman, Luc, 1970- (ROUTLEDGE, 2025)
This book provides a concise guide to navigating, mapping, and understanding the complexity of political mechanisms and narratives behind transport cooperation.Transport is a constant political object of conflict, cooperation, and negotiation, irrespective of the type of transport or the place where the mobility of people and goods is an issue. The number of actors engaged in transport decision-making, and the technical nature of the mobility issues, appears to make cooperation between transport stakeholders increasingly complex. Drawing on clear analytical devices, visual tools, and insightful illustrations, Transport Diplomacy navigates this complexity and considers a path towards a sounder dialogue in the transport arena. Providing accessible and digestible insights across six chapters, the book explores different semiotic dimensions of these transport planning narratives and cooperation processes.This offers practitioners, decision-makers, and researchers a common conceptual approach to the diplomatic dimension of transport planning. In doing so, it envisages transport planning as not only a procedural set of techniques to implement informed mobility solutions but also a field of managing conflicting narratives and rhetoric by actors with diverging or compatible interests. This book will appeal to those working in transport, mobilities, and planning.